Etika Murid dan Guru Menurut Imam Al-Ghazali Dalam Kitab Ihya-Ulumuddin - Lasmi Rambe (Medan Resource Center, 2021)
Ethics is a science that studies good and bad deeds in the process of carrying out an activity. Ethics is very important for life, especially ethics in the process of obtaining usefel knowledge. The importance of ethics emphasizes that ethics must be studied and applied, especially in the field of education in the process of gaining knowledge. Thinking about the ethics of elerning and learning, is the figure of Imam al-Ghazali, who is one of the scholars who understands the importance of ethics in a person. So I was interested in researching the thoughts og Imam al-Ghazali. The purpose of this research is to make us more aware of and apply the importance of an ethics that we must cultivate in ourselves, especially in the process of gaining knowlodge. In this study, the author uses quantitavive methods, namely conducting library research with data collection techniques by recording, analyzing, reading, and managing research from various books and scientific works that support this research by prioritizing primary data